STRENGTHENING RELIGIOUS HARMONY THROUGH COMMUNITY PARTICIPATION AND LOCAL WISDOM IN TARAKAN CITY - Rais, Muhammad; Syarifuddin, Syarifuddin; Mukhtar, Andi Hijaz (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2025)
In the past five years, the Religious Harmony Index in North Kalimantan Province has shown a consistently high level of achievement, remaining above the national average. In 2021, the index recorded a score of 75.63, surpassing the national average of 72.39. This study seeks to explore the key factors behind this sustained harmony, focusing on how social, cultural, and institutional dynamics contribute to the province’s strong interreligious relations. Employing a qualitative research approach, the study was conducted in Tarakan City—a heterogeneous urban setting considered representative for examining the drivers of religious harmony in the region. The data were collected through interviews, observations, and documentation, and analyzed using a descriptive qualitative method. The findings reveal that one of the primary factors contributing to the high Religious Harmony Index in Tarakan is the active role of the Forum Kerukunan Umat Beragama (FKUB) or the Interfaith Harmony Forum. Through consistent dialogue and coordination among religious leaders, FKUB plays a strategic role in maintaining social cohesion and resolving emerging issues at the grassroots level before they escalate publicly. The forum also identifies potential sources of intolerance and applies cultural approaches in mediating community conflicts, such as disputes related to the establishment of houses of worship. Another significant factor is the preservation of local wisdom among the Tidung ethnic community, particularly the values embodied in tenguyun—a tradition that emphasizes cooperation, mutual assistance, and communal solidarity. These cultural principles extend to environmental stewardship, reflected in the Tidung people’s moral responsibility to protect natural ecosystems such as mangrove forests. Overall, this study underscores that cultural communication and local wisdom function as vital socio-cultural capital that reinforce institutional efforts to sustain religious harmony. These findings highlight the importance of integrating local cultural values into broader peacebuilding frameworks to strengthen interfaith relations in plural societies .